Criminological determinants of the overuse pre-trial detention: Criminological determinants of the overuse pre-trial detention (Archives of Criminology, 2023)
In recent years, Poland has observed an increase in the number of people in pre-trial detention. At parallel, crime rates are not high and are on declining trend. There is therefore a tendency which defies the logical, natural justification that the number of pre-trial detentions should increase in line with the growth of crime, especially the most serious types of crimes. The article discusses purposes and functions of detention in Polish criminal procedure. The analysis of them indicates that the illegal use of non-procedural functions, which is facilitated by certain factors, may lead to overused pre-trial detention in Poland.